Légvédelem . Air defense ([Budapest])
The usual images of our peaceful life - people enjoying a walk on the streets in springtime or relaxing in the warmth of their homes - create a sense of security. Nevertheless, the life and security of each and every one of us is in our own hands. We must know how to respond to an unexpected crisis caused by a nuclear strike. Since the success of our defense greatly depends on our familiarity and compliance with the rules and regulations of emergency scenarios, we must know how to behave when the air raid sirens are sounded. We must also know the rules pertaining to the use of public shelters, right from their construction through the equipment found there and their proper use, all the way down to the code of civilian conduct in the shelters. Békés életünk megszokott képei, az utcán megtett tavaszi séták, az otthon melege a biztonság érzetét keltik bennünk. Saját életünkért és mások biztonságáért azonban mindannyian felelősek vagyunk, ezért tudnunk kell, hogyan reagáljunk egy váratlan krízisre, amit egy atomtámadás okozhat. A sikeres védelem nagyban múlik a szabályok ismeretén és betartásán, ezért tudnunk kell, hogy mi a teendő a légoltalmi készültségbe helyezésnél. Ismernünk kell az óvóhelyekre vonatkozó szabályokat, azok kialakításától a felszerelésén át egészen a használatig, az óvóhelyi civil magaviselet kódexéig.